2010
DOI: 10.1063/1.3366718
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the thermodynamic signatures of hydrophobic hydration for several common water models

Abstract: Following the conclusions of an information theory analysis that hydrophobic hydration is dictated by the equation of state of liquid water, we perform simulations of ten different water models to examine the correlation between the fidelity of each model to the experimental density of liquid water and the accuracy of its description of methane hydration. We find that the three- and five-point water models provide an inferior description of both the liquid density and methane solubility compared to the four-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 49 publications
10
63
0
Order By: Relevance
“…One possible source of such biases is the overestimation of hydrophobic interactions by the current force field. This view is in line with prior simulation results that showed that the hydration free energies of non-polar molecules are systematically overestimated 19,[21][22][23] . In an effort to remedy such discrepancies, relevant protein/water interaction terms in the force field may need to be further optimized.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…One possible source of such biases is the overestimation of hydrophobic interactions by the current force field. This view is in line with prior simulation results that showed that the hydration free energies of non-polar molecules are systematically overestimated 19,[21][22][23] . In an effort to remedy such discrepancies, relevant protein/water interaction terms in the force field may need to be further optimized.…”
Section: Resultssupporting
confidence: 80%
“…As for the force field, we use the ff99sb-nmr1-ildn force field (nmr1) 13,14 for the protein segment. The nmr1 force field is a highly optimized version of its parent force field ff99sb 13 18,19 . In contrast with the tip3p model, the tip4p/2005 model 16 (an improved version of its parent tip4p model 15 ) can reproduce various experimental temperature-dependent properties.…”
mentioning
confidence: 99%
“…This stands in contrast to the common view according to which the solvation of hydrophilic solutes is purely enthalpic and characterized by vanishing heat capacity. 22,23 We note, that the solvation free energies for a Lennard-Jones parameterization of methane 40 are well within the spread observed in Fig. 10(e).…”
Section: Influence Of Attractive Interactionssupporting
confidence: 60%
“…(17) is not very serious, as shown in Figs. 8(c) and 8(d), one concludes that it is mostly the variation in ρ that causes the differences in the solvation free energy, 27,37,40 as seen in Figs. 8(a) and 8(b).…”
Section: Influence Of Water Models Comparison With Information Thmentioning
confidence: 94%
See 1 more Smart Citation